Ageing with style in Singapore : Crazy Old Asians - Chua, Eunice Chia Woon (Nanyang Technological University, 2021)
Ageing With Style in Singapore: Crazy Old Asians is a collection of three feature news stories that celebrate the cool and unconventional ways seniors can age in Singapore, which by 2050 will be in the top 10 countries in the world with the highest percentage of people above 60.